2020
DOI: 10.1021/acsnano.0c03961
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Infused Porous Surfaces for Robust, Thermally Conductive, Self-Healing Coatings for Dropwise Condensation

Abstract: Hydrophobic coatings with low thermal resistance promise a significant enhancement in condensation heat transfer performance by promoting dropwise condensation in applications including power generation, water treatment, and thermal management of high-performance electronics. However, after nearly a century of research, coatings with adequate robustness remain elusive due to the extreme environments within many condensers and strict design requirements needed to achieve enhancement. In this work, we enable lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 56 publications
0
26
0
Order By: Relevance
“…Liquid infused surfaces (LIS) have been shown to enhance droplet mobility in condensation applications, by dramatically reducing contact angle hysteresis, however the gradual loss of lubricant could make the effect short lived. [31,[36][37][38][39] Polymer infused porous surfaces also offer low contact angle hysteresis and tunability, as well as being more robust than LIS, however they are complex to fabricate and may be challenging to scale up. [37] Only recently, Cha et al have shown that a less complex hydrophilic surface with low contact angle hysteresis, can determine efficient dropwise condensation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liquid infused surfaces (LIS) have been shown to enhance droplet mobility in condensation applications, by dramatically reducing contact angle hysteresis, however the gradual loss of lubricant could make the effect short lived. [31,[36][37][38][39] Polymer infused porous surfaces also offer low contact angle hysteresis and tunability, as well as being more robust than LIS, however they are complex to fabricate and may be challenging to scale up. [37] Only recently, Cha et al have shown that a less complex hydrophilic surface with low contact angle hysteresis, can determine efficient dropwise condensation.…”
Section: Introductionmentioning
confidence: 99%
“…[31,[36][37][38][39] Polymer infused porous surfaces also offer low contact angle hysteresis and tunability, as well as being more robust than LIS, however they are complex to fabricate and may be challenging to scale up. [37] Only recently, Cha et al have shown that a less complex hydrophilic surface with low contact angle hysteresis, can determine efficient dropwise condensation. [40] This paper focuses on the droplet nucleation and coalescence part of the condensation process.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 However, when the surface is hydrophobized by coating it with a promoter material (for example, silane treatment), vapor condenses in dropwise mode (discrete water droplets). [14][15][16] Numerous studies have demonstrated that phase-change heat transfer during dropwise condensation is nearly an order of magnitude higher than filmwise condensation in a pure vapor environment since in the latter mode of condensation, the continuous liquid film adds a conduction resistance (thermal barrier) to heat transfer. Furthermore, during dropwise condensation, the periodic shedding of discrete water droplets when they reach the capillary length (≈2.7 mm for water at 25 °C and 1 atm) improves the phase-change heat transfer rate by exposing the condensing surface to vapor in addition to refreshing active nucleation sites.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, achieving stable hydrophobicity with these materials relies on developing hydrophobic coatings, which are commonly made from perfluoro-compounds (PFCs) due to their low surface energy (5-20 mJ•m −2 ) 11 . However, PFC coatings are not able to achieve long-term hydrophobicity (1-year long lifetime) for many applications because they lack mechanical robustness [12][13][14][15] . Recent work has shown that surface defects such as pinholes or scratches lead to significant shortening of coating lifetime.…”
mentioning
confidence: 99%
“…Some of the most important include dropwise condensation 15,21 , atmospheric water harvesting 12 , and water desalination 22 , where the heat and mass transfer rate can be enhanced by an order of magnitude by using hydrophobic surfaces, with the merit of these offset if the coating is thick (h > 100 nm) and thermally insulating 15,23 . Although in recent years significant effort has been placed on designing thick and thermally conductive composite materials to overcome this challenge, scalable fabrication techniques for these coatings remain elusive 14,20 . The importance of defect prevention has been increasingly realized for improving the durability of thin hydrophobic coatings.…”
mentioning
confidence: 99%